Tourism Sector and Regional Income Relationship in Sinjai - Khusniati, Navi'ah; Hermansyah, Fakhrul Indra (Faculty of Economics and Business, Hasanuddin University, 2023)
Several previous studies have revealed that the tourism sector is positively related to regional income (pendapatan asli daerah). Even though the selected research location still does not have tourism potential, the relationship between these two variables is important to discuss to find tourism potential in Sinjai Regency. This research uses quantitative analysis with the ErrorCorrection Model (ECM) approach, which shows that all variables have fulfilled the stationarity test, long-term cointegration, Error-Correction Term (ECT) and the classical assumption test (Boedijoewono, 2012), which is the time data-series from 2012 to 2021 is used to include proxies for the number of tourists, number of hotels and other accommodation, level of infrastructure, Gross Regional Domestic Product (GDRP) in the tourism sector (trade, hotel and restaurant, entertainment and recreation sectors) and Original Regional Income in Sinjai Regency. The results of this research reveal that in the short term, changes in PAD are influenced simultaneously and partially by changes in the number of tourists, the length of roads in good condition, and Tourism GRDP. However, changes in PAD are not influenced by changes in the number of hotels. On the other hand, every change in the number of tourists and the length of road conditions will have an influence on changes both simultaneously and partially in PAD. Finally, the number of hotels and tourism GRDP do not have a significant influence on PAD.